Differences in athletic identity, sport participation, and psychosocial factors following anterior cruciate ligament rehabilitation in youth athletes - McGinley, James; Stapleton, Emily; Gale, Emily; Worrall, Hannah; Podvin, Caroline; Ellis, Henry B.; Wilson, Philip L.; Ulman, Sophia (Frontiers in Psychology, 2024)
Introduction While youth sports benefits the developing athlete, athletes may also be subject to injury and subsequent return-to-sport protocols. The current return-to-sport criteria emphasize physical measures; however, psychological measures may also be valuable to inform providers of an athlete’s readiness. One such measure is athletic identity defined as the degree to which an individual identifies with the athlete role. To better understand athletic identity in return-to-sport, this study aimed to identify relationships and trends between the Athletic Identity Measurement Scale (AIMS), demographic variables, sport participation measures, and the Athletic Coping Skills Inventory-28 (ACSI-28) in youth athletes during rehabilitation following anterior cruciate ligament reconstruction (ACLR). Methods A retrospective review was completed of patients who underwent ACLR at a sports medicine clinic between October 2019 and May 2021. Patients responded to a series of patient reported outcomes (PROs) regarding physical and psychological function at a pre-surgical baseline and after 1 year of rehabilitation. Patients were then divided into groups of high/low AIMS and an increased/decreased AIMS between 1 year and baseline for comparison. Independent samples t-tests and ANOVAs were performed as appropriate with a 95% confidence interval. Results In the final sample, 87 patients (15.3 ± 1.8 years) were included, with 51.7% being females. Total AIMS scores decreased from 50.3 to 47.5 over rehabilitation (p = 0.019). Furthermore, results indicated that nearly all AIMS scores decreased during rehabilitation, with none showing an increase; however, not all domains were significant. Conversely, all sport participation and coping ability PROs increased over time points except for ACSI-Confidence and Achievement Motivation. Generally, those in the groups with high AIMS and an increase in AIMS also had higher scores in physical function and coping ability PROs, with the groups separated by high/low AIMS exhibiting more frequent statistical significance. Discussion Given these results, it appears that athletes may lose identification with the athlete role after ACLR and struggle even 1 year for rehabilitation, but those who recover athletic identity the best may also be those able to cope most effectively with the stressors induced by injury.